2021
DOI: 10.48550/arxiv.2110.15468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interval Estimation of Relative Risks for Combined Unilateral and Bilateral Correlated Data

Abstract: Measurements are generally collected as unilateral or bilateral data in clinical trials or observational studies. For example, in ophthalmology studies, the primary outcome is often obtained from one eye or both eyes of an individual. In medical studies, the relative risk is usually the parameter of interest and is commonly used. In this article, we develop three confidence intervals for the relative risk for combined unilateral and bilateral correlated data under the equal dependence assumption. The proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Pei et al [10] studied ten test statistics to test the equality of two proportions and found that Rosner and Wald-type statistics based on dependency models and constrained maximum likelihood estimation perform satisfactorily for small to large samples. For general g ≥ 2 groups, Wang and Ma [11] worked on the combined bilateral and unilateral data and developed three types of confidence intervals for the relative ratio. Their simulation results show that score tests are always robust under different configurations with the median near the nominal type I error rate, and they yield higher powers than other test statistics, assuming the paired organs are not completely independent.…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [10] studied ten test statistics to test the equality of two proportions and found that Rosner and Wald-type statistics based on dependency models and constrained maximum likelihood estimation perform satisfactorily for small to large samples. For general g ≥ 2 groups, Wang and Ma [11] worked on the combined bilateral and unilateral data and developed three types of confidence intervals for the relative ratio. Their simulation results show that score tests are always robust under different configurations with the median near the nominal type I error rate, and they yield higher powers than other test statistics, assuming the paired organs are not completely independent.…”
Section: Introductionmentioning
confidence: 99%